Progress in the study of cholupa (Passiflora maliformis L.) phenology in producing areas of Colombia (2020)
The cholupa or stone granadilla (Passiflora maliformis L.) is one of the eight cultivated species in the genus Passiflora L. However, the phenological development of this species has not been investigated. This study aimed to assess some phenological aspects of cholupa growth in the vegetative and reproductive phases in the town of Rivera (Colombia). The plant phenology during the vegetative and reproductive phases of growth was evaluated with weekly measurements of the length and number of stem nodes, primary and secondary branches, and longitudinal and transverse fruit diameters in commercial crops. The curves described the dynamics of growth in the main stem and primary and secondary branches and their respective equations using the curve fitting technique, which was fit to sigmoidal-logistic models with high statistical reliability. The time from anthesis to fruit maturity was between 50 and 60 days; the final longitudinal and transverse diameters averaged 54 and 53 mm, respectively. The phenological BBCH scale was established for the major phenological stages (E1: leaf development of the main stem, E3: stem elongation, E5 and E6: appearance and development of floral organs and flowering, and E7: fruit development). These aspects of cholupa development were similar to reports on other Passiflora species, providing very useful results for defining agronomic practices in cultivation and breeding programs.